Investigating the relationship between prenatal androgen exposure and sleep quality: a comprehensive study using anthropometric measurements, questionnaires, actigraphy, and polysomnography - Bartoszek, Adrian; Sawic, Magdalena; Pierzchała, Karol; Kudrycka, Aleksandra; Białasiewicz, Piotr; Kuczyński, Wojciech (Frontiers in Endocrinology, 2025)
BackgroundThe 2D:4D digit ratio (DR), representing the relative length of the index finger to the ring finger, is an anthropometric marker that shows sexual dimorphism, with males typically having a lower ratio than females. This parameter is linked to prenatal androgen exposure (PAE), which influences sexual differentiation of the brain and behavior. This study aimed to investigate the correlation between PAE and sleep among young adults.MethodsAnthropometric measurements were used to assess PAE, while sleep was evaluated using the Pittsburgh Sleep Quality Index (PSQI), Morningness-Eveningness Questionnaire (MEQ), actigraphy, and polysomnography (PSG). Data was collected from 720 participants via surveys, with 290 completing all questionnaires. Of these, 138 underwent anthropometric measurements, and 38 were further recruited for actigraphy, PSG.ResultsMen exhibited a lower 2D:4D ratio than women, indicating higher PAE. The average PSQI score was 6.94 ± 2.98, and the MEQ score was 35.43 ± 19.59, with no significant gender differences in sleep quality or chronotype. Low PAE was associated with better sleep efficiency and a morning chronotype, but worse sleep quality in males. Actigraphy results showed no significant differences based on PAE. PSG data revealed that males with longer 2nd fingers and higher 2D:4D ratios were more likely to suffer from mild sleep apnea, a pattern not observed in women. PAE did not significantly impact other sleep architecture parameters.ConclusionsPAE, indicated by the 2D:4D ratio, is linked to sleep efficiency and chronotype, with significant gender differences. Men with lower PAE exhibited poorer sleep quality, and those with certain finger length patterns were more prone to mild sleep apnea. These findings underscore the potential long-term impacts of PAE on sleep health and emphasize the need for further research into gender-specific sleep regulation mechanisms.